Combining First-Person Video and Gaze-Tracking in Medical Simulation: A Technical Feasibility Study. (19th February 2014) - Szulewski, Adam; Howes, Daniel
Abstract : Crisis decision-making is an important responsibility of the resuscitation team leader but a difficult process to study. The purpose of this pilot study was to explore the potential of gaze-tracking technology to study decision-making and leadership behaviours in simulated medical emergencies. We studied five physicians with a broad range of experience in a simulated medical emergency using gaze-tracking glasses. Subjects were interviewed immediately after the scenario while viewing a first-person recording of their performance with a superimposed gaze indicator. The recordings were then studied independently by two reviewers, and rated for quality and their observations collated. Portable gaze-tracking devices were found to be useful and effective tools for studying information gathering and decision-making behaviours in simulated medical emergencies. The data obtained in this study provided information about the discrepancy between what each participant looked at compared to what each participant consciously noted. Analysis of the data also identified a number of recurrent gaze patterns performed by team leaders that could be used as end-points in future research. Gaze-tracking in resuscitation medicine is a new and promising field of study. The potential to study crisis decision-making behaviours, and cognitive load, as well as differences between novice and expert team leaders is substantial.